Analysis of Science Literacy and Environmental Awareness of Elementary School Students Through the Use of STEM-Based Solar Sprinkle and Ecoburn Media in Science Learning - Wati Sukmawati; Hendely A. Adlawan; Najla Delfina Andarawan (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study is to examine the effectiveness of STEM-based learning media, namely Solar Sprinkle and Ecoburn, in enhancing science literacy and environmental awareness among elementary school students. This quantitative study employed a pre-experimental design with a one-group pretest-posttest involving 50 students. Data were collected using standardized instruments measuring science literacy and environmental awareness. The results indicated a significant overall improvement in both variables after the intervention. The findings suggest that interactive, STEM-oriented media can support the development of students' understanding of scientific concepts and foster greater awareness of environmental issues. In conclusion, the integration of Solar Sprinkle and Ecoburn in science learning proved effective in promoting science literacy and environmental responsibility in the primary education context